Utilization of Solar Energy for Filtering Water System - Abdul Rahim, Muhammad Khairul Anwar; Lilywati Bakar,; Zurina Abdul Wahab, (Progress in Engineering Application and Technology, 2024)
This project "Utilization of solar energy for water filtration systems" explores the potential of solar energy to power water filtration systems. Solar offers a clean and renewable alternative to traditional energy sources, reducing dependence on fossil fuels. The system offers low operating costs after initial installation, as it uses free solar energy. Furthermore, its off-grid capabilities make it ideal for remote locations that do not have access to electricity. Although cost savings can be achieved through the use of economical materials such as used solar panels or locally sourced components, the overall cost of the system depends on the specific components selected. In addition, cost savings can be applied when an in-depth analysis is done regarding the amount of electrical power required to enable this system to function. Therefore there is no excess cost used as the goods used are excessive and consume high costs.